Queer: a Philosophy Phenomenon, a Social Construct, a Language Sign - MARCHYSHYNA, Alla Anatolii; SKRYPNYK, Anatolii (WISDOM, 2019)
The paper considers ontology of queer as interpreted in philosophy, social studies and language. The short history of the analysed concept sheds light on transformations of its semantic structure. Queer is viewed inseparably from gender theory where it gets apparent representation as a queer gender identity. The diffusive and trespassing nature makes queer contrary to stable and traditionally immutable sex/gender dichotomy with the normative male/female components. Queer violation of this long-established standard results in revolutionary shifts in the philosophy of human sex/gender freedom of manifestation and recognition, formation and alteration of social stereotypes, introduction and spread of verbal means serving the lingual signs of queer in general and queer gender identity, in particular. Texts of scholarly, publicist and literary functional styles depict “queer” differently depending on the objectives of each register and the appropriate scope of linguistic tools.